Sociological Implications on Safety of Journalism as a Profession in Nigeria - Folorunsho Muyideen Ogunmefun; Raheem Olalekan Akeem (Randwick International of Social Science Journal, 2020)
All over the world, Journalists are known as the fourth realm of the Estate charged with the responsibility of disseminating information to the societal members. Despite the contribution of the noble profession towards nation building, large number of journalist in the past and recent time in Nigeria faces series of challenges ranging from kidnapping, assault, harassment, torture, arbitrary detention, murder, imprisoned at the virtue of saving the nation. The gravity and magnitude of the prevalence insecurity in the profession has gotten to a state of psychological trauma and lost of interest for the profession. Several publications were reviewed; Anomie (Robert Merton) and Situational Crime Prevention (Ronald Clarke) theories were adopted. Qualitative method and purposive sampling technique was adopted in conducting in-depth interviews among 10 public members and 25 journalists from 4 media print Organisations, 3 radio stations and 2 television stations in Nigeria, In Nigeria journalist are faced with numerous insecurity issues and there is an urgent need to readdress the issues to save the nation from retrogressive development. Several recommendations are stated to safe the profession( a) the struggle for the survival of the profession should not be left alone to either the Government or the journalists it should be collectively addressed by all, More so, proactive methods, deterrence measures target hardening, access and facilitators control needs to be in placed to tackle the menace